Quick and stable parallel puncture of hepatic tumors using a double‐barreled needle direction system for ultrasound‐guided bipolar radiofrequency ablation. Issue 11 (15th March 2016) - Sakakibara, Mitsuru; Ohkawa, Kazuyoshi; Imanaka, Kazuho; Miyazaki, Masanori; Nawa, Takatoshi; Kimura, Haruki; Abe, Yutaro; Katayama, Kazuhiro
Abstract : Aim: In bipolar radiofrequency ablation (RFA) therapy, insertion of multiple needles at appropriate points on a target is difficult. The aim of our study was to evaluate a simplified method for multi‐electrode insertion using a newly developed double‐barreled needle guidance system for percutaneous RFA of hepatic tumors. Methods: RFA using two bipolar electrodes was performed in 15 consecutive patients (nine men, six women; mean age, 72.0 ± 8.2 years) with a solitary small (≤3 cm) hepatic tumor. The first five nodules were treated using the conventional puncture method with the standard attachment, then 10 nodules were ablated using the parallel puncture method with the double‐barreled attachment. The times required for double‐needle placement and the shapes of the ablated areas were compared between the two puncture methods. Results: The parallel puncture method required a shorter time for double‐needle placement than the conventional method (12 s [range, 8–24] vs 96 s [range, 50–240]; P = 0.0003), and allowed continuous observation of the tip of all needles and the size of the ablated area as it increased until completion of the ablation. The method also provided a stable ellipsoidal ablated area. The median height, width and thickness were 30 mm (range, 22–34), 30 mm (range, 21–33) and 20 mm (range, 7–25), respectively, using 20‐mm electrodes, and 34 mm (range, 32–41), 36 mm (range, 35–38) and 24 mm (range, 23–24), respectively, using 30‐mm electrodes. Conclusion: The parallel puncture method may be a feasible procedure for multi‐needle RFA therapy.